New data on the apophytic occurrence of Epipactis helleborine (L.) Crantz and Cephalanthera longifolia (L.) Fritsch in Populus x canadensis plantation in Lower Silesia (south-western Poland) - Jakubska, Anna; Malicka, Maria; Malicki, Marek (Biodiversity: Research and Conservation, 2006)
In the course of the research, two species of orchids, i.e. Cephalanthera longifolia (L.) Fritsch and Epipactis helleborine (L.) Crantz have been found to appear in large quantities in poplar monoculture Populus xcanadensis in the Krzyżowe Hills (Lower Silesia, Poland). No data on sword-leaved and broad-leaved helleborine occurrence in such habitats in Lower Silesia have been published so far. Based on the list of species accompanying Cephalanthera longifolia and Epipactis helleborine, the habitat analysis has been conducted by means of Ellenberg's ecological indicator values. For the first time Cephalanthera longifolia is reported in Populus xcanadensis monoculture in Poland.